2009
DOI: 10.1002/cbdv.200900003
|View full text |Cite
|
Sign up to set email alerts
|

abeo‐Taxane Diterpenoids from the Taiwanese Yew Taxus sumatrana

Abstract: Chemical investigation of the acetonic extract of the leaves and twigs of Taxus sumatrana (Taxaceae) led to the isolation of four new taxane diterpene esters, taiwantaxins A-D (1-4, resp.). Their structures were determined primarily on the basis of 1D- and 2D-NMR techniques as well as MS. Compound 1 is a rearranged taxane diterpenoid possessing an opened oxetane ring moiety containing C(4), C(5), and C(20). The metabolites 2 and 3 belong to a 5/6/6 taxene system having a rare five-membered gamma-lactone ring c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…Its 13 C NMR spectrum showed resonances for four carbonyls (δ C 206.1, 193.5, 170.8, 166.7), four methyls (δ C 23.2, 22.8, 17.9, 8.9), a pair of olefinic carbons (δ C 166.9, 137.3), a methine (δ C 45.2), an anomeric carbon (δ C 104.4), six oxymethines (δ C 85.2, 77.8, 76.0, 74.3, 70.5, 69.4), three methylenes (δ C 40.0, 37.0, 27.5), two oxymethylenes (δ C 76.0, 66.0), two quaternary carbons (δ C 69.8, 56.2), two oxygenated quaternary carbons (δ C 90.7, 80.0), and an aromatic ring (δ C 129.2–133.5) (Table ). The NMR data of the aglycone moiety of 5 resembled closely those of 15-benzoyl-10-deacetyl-2-debenzoyl-10-dehydro-11(15→1) abeo -baccatin III, except for the presence of a methylene in 5 instead of an oxymethine proton assigned for C-13 . Therefore, 5 was suggested to be a 9,10-diketo- abeo -taxoid glycoside.…”
Section: Resultsmentioning
confidence: 94%
“…Its 13 C NMR spectrum showed resonances for four carbonyls (δ C 206.1, 193.5, 170.8, 166.7), four methyls (δ C 23.2, 22.8, 17.9, 8.9), a pair of olefinic carbons (δ C 166.9, 137.3), a methine (δ C 45.2), an anomeric carbon (δ C 104.4), six oxymethines (δ C 85.2, 77.8, 76.0, 74.3, 70.5, 69.4), three methylenes (δ C 40.0, 37.0, 27.5), two oxymethylenes (δ C 76.0, 66.0), two quaternary carbons (δ C 69.8, 56.2), two oxygenated quaternary carbons (δ C 90.7, 80.0), and an aromatic ring (δ C 129.2–133.5) (Table ). The NMR data of the aglycone moiety of 5 resembled closely those of 15-benzoyl-10-deacetyl-2-debenzoyl-10-dehydro-11(15→1) abeo -baccatin III, except for the presence of a methylene in 5 instead of an oxymethine proton assigned for C-13 . Therefore, 5 was suggested to be a 9,10-diketo- abeo -taxoid glycoside.…”
Section: Resultsmentioning
confidence: 94%
“…The tasumatrols A-Z were reported isolated from leaves and twigs [10][11][12][13][14][15]. The leaves and twigs also isolated Taiwantaxins A-D isolated [16] and other chemical compounds [17,18]. Some of the isolated compounds reported have cytotoxic activities.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the isolated compounds reported have cytotoxic activities. Among them are wallifoliol (KB and Hepa 59 T/VGH), taxuspine F, and 3, 6, 7, 10-deacetylbaccatin III (Hepa cells), tasumatrol F (A-498, NCI-H226, A549, and PC-3 tumor cells), Tasumatrols I and K (Hepa59T/VGH, NCI, HELA, DLD-1, and Med cell lines), tasumatrol P (HELA and Daoy tumor cells), tasumatrol Z (Hep2 cell line), and Taiwantaxin B (PC-3 tumor cells) [9][10][11][12][13][14][15][16][17]. The results of clinical studies also indicated that paclitaxelcontaining regimens on breast cancer patients provided additional benefits [19].…”
Section: Introductionmentioning
confidence: 99%